Unfair treatment of worker and occupational stress - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2017)
Occupational stress in the present globalised world is fraught with tremendous concern to the employees and other stakeholders of organisations. Excessive workload or work demand, and stressful deadlines, long working hours, insufficient number of staff, lack of support from co-workers and supervisors, annoying coworkers, angry customers, hazardous working conditions, job uncertainty and hostile work environment, among others are some of the commonly known stressor that contribute to occupational or workplace stress. Workplace stress often shows high dissatisfaction among the employees in terms of job mobility, burnout, less effective interpersonal relations at work and unsatisfactory work performance. This may be due to several reasons such as persistent lateness or tardiness, excessive sick leave and repeated absences, among others. Long-term stress or traumatic events at work can affect the physical health of the worker. An employer has a duty to ensure a safe and conducive workplace environment that is free from threats, intimidation and violence. In light of the above, the discussion herein is focused on occupational stress arising from employer's unfair treatment of workers at the workplace.